2018
DOI: 10.1186/s13023-018-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life in children and adolescents with osteogenesis imperfecta: cross-sectional study

Abstract: BackgroundOsteogenesis imperfecta (OI) affects dental and craniofacial development and may therefore impair Oral Health-Related Quality of Life (OHRQoL). However, little is known about OHRQoL in children and adolescents with OI. The aim of this study was to explore the influence of OI severity on oral health-related quality of life in children and adolescents.MethodsChildren and adolescents aged 8–14 years were recruited in the context of a multicenter longitudinal study (Brittle Bone Disease Consortium) that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Tosi et al () reported health issues encountered by adults with OI throughout their lifespan. For instance, about 50% of individuals with OI are born with dentinogenesis imperfecta (Biria, Abbas, Mozaffar, & Ahmadi, ), which affects the quality of life of children, adolescents, and adults (Najirad et al, ). Second, the present review excluded case reports on skeletal manifestations because it was addressed by the OI community (Forlino et al, ; Forlino & Marini, ; Rauch & Glorieux, ), and rather focused on the extra skeletal manifestations of OI due to paucity of research.…”
Section: Discussionmentioning
confidence: 99%
“…Tosi et al () reported health issues encountered by adults with OI throughout their lifespan. For instance, about 50% of individuals with OI are born with dentinogenesis imperfecta (Biria, Abbas, Mozaffar, & Ahmadi, ), which affects the quality of life of children, adolescents, and adults (Najirad et al, ). Second, the present review excluded case reports on skeletal manifestations because it was addressed by the OI community (Forlino et al, ; Forlino & Marini, ; Rauch & Glorieux, ), and rather focused on the extra skeletal manifestations of OI due to paucity of research.…”
Section: Discussionmentioning
confidence: 99%
“…Najirad et al, demonstrated that the severity of OI impacts OHRQoL in adolescents aged 11 to 14 years. Scores were higher (i.e., worse) for type lll and IV than for type l. Differences were associated with a signi cantly higher grade of functional limitations on OI types lll and IV compared to OI type I (9). Furthermore, according to Rizkallah and colleagues' analysis of the peer assessment rating and discrepancy index, individuals with OI have signi cantly lower estimates for ve malocclusion traits than the general population, including anterior open bite, posterior open bite, anterior crossbite, posterior crossbite, and Angle classi cation III (11).…”
Section: Introductionmentioning
confidence: 87%
“…In 2007, a measurement method for very young children was developed, the Early Childhood Oral Health Impact Scale (ECOHIS) (Pahel et al, 2007). So far, at least eight reports have investigated OHR‐QoL in patients with rare genetic bone diseases (Aarts et al, 2023; Gjørup et al, 2021; Hanisch, Bohner, et al, 2019; Hanisch, Sielker, et al, 2019; Najirad et al, 2018, 2020; Nguyen et al, 2019; Oelerich et al, 2020) (Table 3). The most frequently used method for measuring OHR‐QoL is OHIP‐14, a shortened form of the original OHIP‐49 that captures seven domains of OHR‐QoL with two items per domain: functional limitation, physical pain, psychological discomfort, physical disability, psychological disability, social disability, and handicap.…”
Section: Influence Of These Diseases On Patients' Ohr‐qolmentioning
confidence: 99%
“…All questions relate to the frequency of events in relation to the condition of the mouth or teeth over the previous four weeks (CPQ8–10) or three months (CPQ11–14). According to Najirad and colleagues, the severity of OI affects OHR‐QoL in adolescents aged 11–14 years, but not in children aged 8–10 years (Najirad et al, 2018). In addition, adolescent OI patients aged 11–14 years with posterior crossbite or open bite had statistically significantly higher CPQ11–14 scores than those without (Najirad et al, 2020).…”
Section: Influence Of These Diseases On Patients' Ohr‐qolmentioning
confidence: 99%